Impacts of Nanoplastics on the Viability and Riboflavin Secretion in the Model Bacteria Shewanella oneidensis - Fringer, Victoria S.; Fawcett, Liam P.; Mitrano, Denise M.; Maurer-Jones, Melissa A. (Frontiers in Environmental Science, 2020)
Characterizing the impact of nanoplastics to organism health is important to understand the consequences of the environmental plastic waste problem. This article examines the impact of nano-polystyrene (nano-PS; 159±0.9 nm diameter) to ecologically relevant bacteria Shewanella oneidensis. Bacterial viability was evaluated using a growth-based assay. Riboflavin secretion is a critical cell function of S. oneidensis, serving as an electron mediator in anaerobic respiration and/or as a signaling molecule when the bacteria are under stress. Thus, changes in cellular function were monitored through riboflavin secretion in order to evaluate toxic responses that may not result in cell death. Under aerobic and anaerobic exposures (4, 8 or 12 h), the viability of the S. oneidensis was minimally changed as compared to the control, while the concentration of riboflavin secreted varied with exposure dose. In order to determine if this was a specific response to nanoplastic particles, opposed to a response to either particles or plastic more generally, we exposed the system to colloidal TiO2 nanoparticles and polystyrene and polyethylene thin films. We confirmed that riboflavin secretion trends were specific to nano-PS and not to these other materials, which showed no significant changes. We investigated the association of the nano-PS with ICP-MS using Pd that was chemically incorporated into the model nanoplastics. While 59.2% of the nano-PS were found in the non-cellular culture media, 7.0% and 6.6% was found associated with the loosely and tightly bound extracellular polymeric substance, respectively. There was significantly more nano-PS (10.9%) strongly associated with the cells. Taken together, we found that nano-PS had minimal impacts to viability but caused a significant change in the function of S. oneidensis that can be related to the nano-PS attached or in proximity to the bacterium. These trends are consistent between aerobic and anaerobic cultures, signifying that the stress response of S. oneidensis can be generalized between different environmental compartments. This work highlights that the association of nanoplastic materials with microorganisms may modify the cellular function that could ultimately be an impact to ecosystem health.